Analisis Berpikir Komputasional Siswa SMP pada Kurikulum Merdeka Mata Pelajaran Informatika - Monalisa, Monalisa (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2023)
The aim of this study was to determine the analysis of students' computational thinking skills on spreadsheets using Microsoft Excel. This type of research is descriptive with the use of qualitative methods. This study used a population of class VII students at SMP Negeri 5 Tangerang. The sample used was 36 students in class VII-G. Data collection was carried out using practicum tests in the computer lab according to the lesson schedule, by assigning the creation of population information tables in Microsoft Excel. The assignment contains all indicators of computational thinking agility including; abstraction, decomposition, algorithm, and data recognition. The ability to think computationally produces student output with a high category of 31%, a moderate category of 50%, and a low category of 19%. Through the results of observations, it can be concluded that students who are in the high category have exceeded all standardized computational capacity indicators. While students in the moderate category show that all indicators of computational thinking capacity have been achieved. Meanwhile, most students who are in the low category have not achieved all the indicators in computational thinking processes.